Abnormal origin of right pulmonary artery from the ascending aorta in an infant (“Hemitruncus”) - Alexandros Tsoutsinos; Ioannis Germanakis; Meletios Kanakis; George Samanidis; Stefanos Despotopoulos; Theofili Kousi; Spyridoula Katsilouli; Olga Karapanagiotou; Dimitrios Bobos (Clinical Case Reports, 2023)
Key Clinical Message Anomalous origin of right pulmonary artery from the ascending aorta is a rare congenital malformation and it needs surgical management. Consequences of this condition affect lead to pulmonary hypertension and severe pulmonary vascular disease. Abstract Anomalous origin of right pulmonary artery from the ascending aorta is a rare congenital heart malformation that results in early infant mortality affecting the right pulmonary artery more than the left. These patients are at risk for the early development of significant pulmonary hypertension. The surgical management during the early period of life is imperative.